Significance of Prolapse Reduction in Measurement of Postvoid Residual Urine Volume in Pelvic Organ Prolapse Patients: A Prospective Study - Tae Young Kim; Moon Kyoung Cho; Chul Hong Kim (IMR Press, 2022)
Background: This study compared postvoid residual (PVR) urine volume by ultrasonography in pelvic organ prolapse (POP) patients before and after prolapse reduction to evaluate the need for prolapse reduction in accurately assessing PVR in women with POP. Methods: This was a prospective study including 128 patients. Both standard methods for measuring PVR urine volume, urethral catheterization, and portable abdominal ultrasound machines were used. An examination was performed by one urogynecologist within five minutes after the patients self-voided. The patients were divided into two groups according to pelvic organ prolapse quantification (POP-Q) stage, early prolapse stage, and advanced prolapse stage, and comparative analysis was performed. Results: Before prolapse reduction, the Pearson correlation coefficient of PVR urine volume measured by ultrasonography and PVR urine volume measured through urethral catheterization was 0.708 in the early prolapse stage and 0.949 in the advanced prolapse stage. After prolapse reduction, the Pearson correlation coefficient of PVR urine volume measured by ultrasonography and PVR urine volume measured through urethral catheterization was 0.895 in the early prolapse stage and 0.982 in the advanced prolapse stage. Conclusions: These study results showed that prolapse reduction when measuring PVR urine volume by ultrasonography in POP patients is acceptable and essential for enhancing accurate patient assessment.